It is with pleasure that we open this second issue of the International Transitions journal by welcoming a new partner.... - d’Anglemont de Tassigny, Alexandra; Frouté, Philippe (International Transitions, 2024)
It is with pleasure that we open this second issue of the International Transitions journal by welcoming a new partner, the ASAP observatory, dedicated to the study and analysis of the impacts of social and societal transformations on public action, led by Professor Olivier Meier. This partnership will undoubtedly enrich the contributions to understanding transitions published in our journal. In this issue, Olivier Meier presents the observatory as well as his vision of the mutual benefits enabled by this new partnership, which illustrates the dynamism of research on transitions. The second issue of the journal also illustrates the multidisciplinary nature of studies on transitions. It opens with an article by Helen Mundler, Associate Professor in English and Anglo-Saxon Languages and Literatures. Helen Mundler addresses a new literary genre: climate change fiction. This literary genre can be compared to speculative fiction as it draws inspiration from a reality of a world transformed by climate emergencies, a world we might very well know tomorrow.